Identification Michelia alba barks extract using Gas Chromatography-Mass Spectrometry (GC-MS) and its antifungal properties to inhibit microbial growth - I Made Dira Swantara; I Gusti Agung Gede Bawa; Dewa Ngurah Suprapta; Kadek Karang Agustina; I Gede Rai Maya Temaja (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Swantara IMD, Bawa IGAG, Suprapta DN, Agustina KK, Temaja IGRM. 2020. Identification Michelia alba barks extract using Gas Chromatography-Mass Spectrometry (GC-MS) and its antifungal properties to inhibit microbial growth. Biodiversitas 21: 1541-1550. Fungicides are substances that inhibit the growth or kill the pathogenic fungi. A substance can be categorized as a fungicide if it shows antifungal activity. This activity is resulting from bioactive compounds derived from the secondary metabolites. Michelia alba bark’s extract could inhibit the growth of Curvularia verruculosa, the cause of leaf spot disease on rice. The purpose of this study was to analyze chemical compounds of bark extract which inhibit the growth of C. verruculosa. The extraction of bark metabolites of M. alba was done using methanol as the solvent. The inhibitory test of the extract was carried out by the diffusion well method on Potato Dextrose Agar (PDA) medium. Analysis of chemical compounds of the M. alba extract was carried out in Gas chromatography-mass spectroscopy. The results of inhibitory test found that the M alba bark extract inhibits the C. verruculosa with the inhibition zone as wide as 36 mm in diameter. The majority of chemical compounds identified from the M. alba extract consisted of 10 compounds, namely: Hexadecanoic acid, methyl ester; 4H-tomentosine; 4H-tomentosine (compound isomer 2); 3-hydroxy pregn-4-ene-20-one; Tomentosine; 2-hydroxy tomentosine; Tert-butyl-2-aminophenylcarbamol; 2H-cyclohepta [b] furan-2-one, 3,3a, 4,7,8,8a-hexahydro-7-methyl-3-methylene-6-(2-formil-3-oxobutyl)-; Isoxanthanol and Xanthanol. To conclude, this extract is useful to treat C. verruculosa that causes leaf spot disease on rice.